2021
DOI: 10.1038/s41467-021-22467-8
|View full text |Cite
|
Sign up to set email alerts
|

ARIH1 signaling promotes anti-tumor immunity by targeting PD-L1 for proteasomal degradation

Abstract: Cancer expression of PD-L1 suppresses anti-tumor immunity. PD-L1 has emerged as a remarkable therapeutic target. However, the regulation of PD-L1 degradation is not understood. Here, we identify several compounds as inducers of PD-L1 degradation using a high-throughput drug screen. We find EGFR inhibitors promote PD-L1 ubiquitination and proteasomal degradation following GSK3α-mediated phosphorylation of Ser279/Ser283. We identify ARIH1 as the E3 ubiquitin ligase responsible for targeting PD-L1 to degradation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(69 citation statements)
references
References 61 publications
0
69
0
Order By: Relevance
“…Particularly, immune costimulatory molecules are one of the recent hotspots in immunology research, and PD-1 and its ligand PD-L1are important participants of tumor progression. PD-L1 is widely expressed in tumor cells, and it binds to PD-1 on the surface of T lymphocytes to transmit inhibitory signals to T cells, thereby inactivating T lymphocyte immune reactions [ 14 , 15 ]. Therefore, inhibition of the PD-1/PD-L1 pathway can enhance T cell function and facilitate tumor cell death, which is a new strategy for tumor therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, immune costimulatory molecules are one of the recent hotspots in immunology research, and PD-1 and its ligand PD-L1are important participants of tumor progression. PD-L1 is widely expressed in tumor cells, and it binds to PD-1 on the surface of T lymphocytes to transmit inhibitory signals to T cells, thereby inactivating T lymphocyte immune reactions [ 14 , 15 ]. Therefore, inhibition of the PD-1/PD-L1 pathway can enhance T cell function and facilitate tumor cell death, which is a new strategy for tumor therapy.…”
Section: Discussionmentioning
confidence: 99%
“…PD-L1 is constitutively expressed on the surface of cancer cells, while the receptor of PD-L1, programmed death protein-1 (PD-1), is mostly expressed on the surface of T cells. Therefore, the interaction between them prevents cancer cells from immune surveillance of T cells ( 111 ). YAP/TAZ and PD-L1 have a bidirectional interaction in suppressing anti-tumor T cell responses.…”
Section: Hippo-yap-regulated Tumor Immunitymentioning
confidence: 99%
“…A study this year further implicated the GSK3α/ARIH1 as another kinase/E3 ligase pair inducing PD-L1 proteolysis. In this case, GSK3α-dependent phosphorylation of PD-L1 at S279/S283 is recognized by the E3 ligase ARIH1, followed by PD-L1 Lys48-ubiquitination and degradation [ 221 ] ( Figure 3 ). Whereas immunocompetent mice are able to reject cancer cell lines overexpressing the ARIH1 E3 ligase, immunocompromised mice are not, reinforcing the crucial role of ARIH1-ubiquitin-dependent pathways in anti-tumor immunity [ 221 ].…”
Section: Ubiquitination Is Essential To Regulate T Cell Activating and Inhibitory Signalingmentioning
confidence: 99%
“…In this case, GSK3α-dependent phosphorylation of PD-L1 at S279/S283 is recognized by the E3 ligase ARIH1, followed by PD-L1 Lys48-ubiquitination and degradation [ 221 ] ( Figure 3 ). Whereas immunocompetent mice are able to reject cancer cell lines overexpressing the ARIH1 E3 ligase, immunocompromised mice are not, reinforcing the crucial role of ARIH1-ubiquitin-dependent pathways in anti-tumor immunity [ 221 ]. Recently, it was revealed that EGFR increases PD-L1 levels by additionally interfering with the membrane-bound MARCH8 E3 ligase, which also targets PD-L1 for degradation [ 222 ] ( Figure 3 ).…”
Section: Ubiquitination Is Essential To Regulate T Cell Activating and Inhibitory Signalingmentioning
confidence: 99%